2021
DOI: 10.18632/aging.202971
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs induce oxidative stress and spermatogenesis by regulating endoplasmic reticulum genes and pathways

Abstract: Oligozoospermia or low sperm count is a leading cause of male infertility worldwide. Despite decades of work on non-coding RNAs (ncRNAs) as regulators of spermatogenesis, fertilization, and male fertility, the literature on the function of long non-coding RNAs (lncRNAs) in human oligozoospermia is scarce. We integrated lncRNA and mRNA sequencing data from 12 human normozoospermic and oligozoospermic samples and comprehensively analyzed the function of differentially expressed lncRNAs (DE lncRNAs) and mRNAs (DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 82 publications
1
19
0
Order By: Relevance
“…lncRNAs were transcribed by RNA polymerase II, then modified by cap at the 5′end and splicing and polyadenosine acidification at the 3′end [ 28 ]. At first, it was thought to have no biological function, but the results of many experiments tell us that lncRNAs regulate gene expression at many levels in the form of RNA, such as transcription, posttranscriptional level, and epigenetics [ 29 , 30 ]. lncRNAs work mainly through the following four ways: first, induction, lncRNAs can bind to a specific miRNA, which can indirectly regulate the target gene; second, lncRNAs can act as a signal molecule on the pathway and regulate the upstream- and downstream-related genes of its target gene [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs were transcribed by RNA polymerase II, then modified by cap at the 5′end and splicing and polyadenosine acidification at the 3′end [ 28 ]. At first, it was thought to have no biological function, but the results of many experiments tell us that lncRNAs regulate gene expression at many levels in the form of RNA, such as transcription, posttranscriptional level, and epigenetics [ 29 , 30 ]. lncRNAs work mainly through the following four ways: first, induction, lncRNAs can bind to a specific miRNA, which can indirectly regulate the target gene; second, lncRNAs can act as a signal molecule on the pathway and regulate the upstream- and downstream-related genes of its target gene [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…One more article was also excluded, as it was a perspective and did not present original data. Finally, a total of 20 articles remained to be included in the present systematic review [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, Sun et al (2021) [ 37 ] examined the expression profile of lncRNAs in oligozoospermia, and found 2364 differentially expressed lncRNAs between oligozoospermic and healthy males. A total of 464 lncRNAs were downregulated, while 1900 lncRNAs were upregulated ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lncRNAs-miRNAs were shown to be involved in the regulation of spermatogenesis, including lncRNA LOC105607399 and LOC105610178. Moreover, another recent study revealed that lncRNAs and mRNAs were abnormally expressed in patients with oligozoospermia and the proportion of downregulated lncRNAs and mRNAs was less than that of upregulated ones [109].…”
Section: Interactions Between Lncrnas Mirna and Mrnas During Spermato...mentioning
confidence: 98%